The Influence of Physical Activity, Fast Food, and Body Composition on Hypercholesterolemia in Young Adults: A Step Toward SDGs - Good Health and Well-being - Sari Hesti Permata; Fadlilah Synta Haqqul; Febriani Ayu Rizky; Yasmin Alya; Fadilah Fitria Nur; Azizah Nisa Fithri (E3S Web of Conferences)
Hypercholesterolemia is a condition marked by elevated cholesterol levels in the blood, which can increase the risk of heart disease, hypertension, and stroke. Lifestyle factors primarily influence this condition. This study examines the relationship between fast food consumption patterns, body composition, and physical activity with blood cholesterol levels. A cross-sectional study was conducted with 100 respondents selected through purposive sampling. Participants were 19-25 yo, non-smokers, and had no Non-Communicable Diseases (NCDs) history. Body composition was assessed using Bio Impedance Analysis (BIA), fast food consumption through a Food Frequency Questionnaire (FFQ), and physical activity using the International Physical Activity Questionnaire (IPAQ). Data were analysed sing Pearson correlation followed by multiple linear regression. The analysis revealed significant relationships between blood cholesterol and per cent body fat (p=0.000; r=0.403), visceral fat (p=0.000; r=0.434), fast food consumption (p=0.000; r=0.528), and physical activity (p=0.000; r=-0.585). The regression analysis indicated that fast food consumption, visceral fat, and physical activity collectively influence blood cholesterol, with correlation coefficients of 0.09, 3.22, and -0.04, respectively. Fast food intake, per cent body fat, visceral fat, and physical activity levels are all associated with blood cholesterol levels.